Cost-utility analysis of lenvatinib and sorafenib for the first-line treatment of unresectable hepatocellular carcinoma in Vietnam: Evidence from a lower-middle income country - Thang Xuan Do; Ha Thi Nguyen; Phuong Thi Lan Nguyen; Mai Thi Tuyet Kieu; Tuan Viet Duong; Van Nu Hanh Pham (PLoS ONE, 2026)
Objectives To evaluate cost-effectiveness of lenvatinib compared with sorafenib as first-line treatment in unresectable hepatocellular carcinoma (HCC) patients in Vietnam from a perspective of the public third-party payer. Methods A three-health state partitioned survival model was developed to compare costs and health outcomes of lenvatinib and sorafenib in unresectable advanced HCC patients over a 10-year time horizon, using a cycle length of 28-day. Clinical data on efficacy and safety of lenvatinib and sorafenib from the REFLECT trial was used to extrapolate outcomes beyond the follow-up period, while medication costs and health care resources were estimated based on local data and clinical experts’ consultations. A discount rate of 3% was applied to both costs and outcomes. Parameter uncertainty was explored using one-way sensitivity analysis and probabilistic sensitivity analysis. The impact of different time horizons and different approaches to extrapolate survival time were examined in scenario analyses. Results In unresectable HCC patients, lenvatinib gained more 0.28 life-years (LYs) equaling to 0.21 quality-adjusted life-years (QALYs) compared with sorafenib. Without consideration of reimbursement rate for all medications and co-insurance, usage of lenvatinib led to an increase of 3,451.3 USD. Therefore, lenvatinib was not cost-effective compared with sorafenib, with an incremental cost-effectiveness ratio (ICER) of 16,114.5 USD/QALY. However, if lenvatinib was reimbursed at the same rate as sorafenib (50%), it became cost-effective, with an ICER of 8,307.6 USD/QALY. Results from the base-case analysis were robust in different sensitivity analyses. Conclusions With a significant improvement in progression-free survival, lenvatinib gained more LYs and QALYs compared with sorafenib. At the same reimbursement rate of sorafenib of 50%, lenvatinib was cost-effective from the perspective of the third-party payer.